Barrier layer, preparation method thereof and solid oxide battery
By using the spin coating method of cerium-based oxide powder and sintering aid in solid oxide batteries, the problems of complex process and poor density in the prior art are solved, and high-efficiency and low-cost barriers are achieved Layer preparation, suitable for large-area single-cell batteries.
Patent Information
- Application Number
- CN202411398913.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The barrier layer preparation process of existing solid oxide batteries is complex, with poor density and uniformity, which limits the preparation and application of large-area single cells.
The cerium-based oxide powder is mixed with sintering aids (such as oxides and salt compounds of Co, Cu, Bi, Li, Zn, Al, Ni) and high density is prepared by spin coating at a lower sintering temperature. , a barrier layer with thin thickness simplifies the process flow.
It realizes a barrier layer with high density, high interface bonding strength and good thickness uniformity, reduces preparation cost and energy consumption, is suitable for large-area single cells, and improves the stability and chemical compatibility of the battery.
Smart Images

Figure CN119297353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a barrier layer and a preparation method thereof and a solid oxide battery, belonging to the technical field of solid oxide batteries. Background Art
[0002] The high-efficiency application of solid oxide cells (SOCs) can be divided into two forms. One is SOFC, i.e. solid oxide fuel cell, which generates electricity by oxidizing fuel; the other is SOEC, i.e. solid oxide electrolyzer, which generates oxygen and hydrogen by electrolyzing water. In principle, SOEC can be regarded as the reverse process of SOFC, which is currently being studied more. As a technology for efficient utilization and conversion of clean energy, solid oxide fuel cell / electrolyzer (SOFC / SOEC) has become one of the important technical means to effectively solve the energy crisis and environmental pollution problems due to its outstanding advantages such as good fuel flexibility and high energy conversion efficiency.
[0003] The interface problems between yttrium-stabilized zirconia (YSZ) electrolyte and active cathode during high-temperature preparation and operation lead to many obstacles such as poor durability of battery stacks and high maintenance costs. Adding a cerium-based oxide (such as gadolinium-doped cerium oxide, i.e., GDC) barrier layer between the electrolyte and the active cathode is an effective solution. Some studies have used methods such as magnetron sputtering and pulsed laser deposition to prepare barrier layers, but low production efficiency and harsh use conditions limit the large-scale mass production development of such processes. Conventional screen printing and spin coating are simple to operate, but the prepared barrier layer usually needs to be co-sintered with the adjacent YSZ electrolyte at a high temperature of ≥1400℃ to obtain relatively high density and interface strength. However, cerium-based oxides and YSZ will react with elements at >1250℃ to generate a high-impedance Ce-Zr solid solution phase, so the application of conventional screen printing and spin coating is limited. Studies have found that the sintering temperature can be reduced to about 1250°C through a multi-step impregnation sintering method, but this greatly increases the complexity and time cost of the process, limiting the actual promotion and application of SOFC / SOEC technology.
[0004] CN111933980A discloses a method for preparing a solid oxide fuel cell. The preparation method mainly includes the following steps: spin coating a barrier layer GDC slurry on a sintered dense electrolyte sheet to obtain a semi-finished battery; pressing the semi-finished battery onto the battery to be prepared for sintering; the battery to be prepared includes a cathode layer, a GDC barrier layer, an electrolyte layer, a GDC barrier layer, and an anode layer in sequence. The preparation method of the solid oxide fuel cell has a simple process, low equipment requirements, and convenient operation; the prepared solid oxide fuel cell has a battery electrode and an electrolyte that are not easy to fall off, which significantly improves the open circuit voltage of the battery. However, the shortcomings of the preparation method of the solid oxide fuel cell mainly include: the battery needs to be pressed and sintered during sintering, and the preparation process requires 1 to 2 sinterings and more than one pre-annealing treatment. Therefore, the preparation conditions and process are complicated, the process is time-consuming, and it is not easy to expand the process to prepare large-area single cells.
[0005] CN113929498B discloses a coating for preparing a barrier layer, a method for preparing a barrier layer, and a barrier layer. The coating for preparing a barrier layer is an aqueous solution including a nitrate and a combustion aid, and the combustion aid is citric acid or glycine. The method for preparing the barrier layer comprises the following steps: applying the coating for preparing the barrier layer to an electrolyte sheet for pre-sintering, decomposing the nitrate to obtain a GDC powder, and obtaining a barrier layer preform; applying a sintering aid to the barrier layer preform, the sintering aid is an aluminum nitrate solution; sintering the barrier layer preform to obtain a barrier layer. However, the method for preparing the barrier layer requires multiple steps of spin coating (4 to 6 times), pre-sintering, and secondary sintering of spin coating with a sintering aid, etc. The process is complicated and the flow is time-consuming, and it is not suitable for preparing large-area single cells.
[0006] CN116364989A discloses a reversible solid oxide fuel cell and its preparation method. The battery includes an electrolyte intermediate layer and barrier layers on both sides thereof, a fuel electrode, and an oxygen electrode, wherein the barrier layer is prepared by introducing small particles into a large particle powder and sintering, thereby achieving densification of the barrier layer. The reversible solid oxide fuel cell is an energy storage device that has the functions of generating electricity using hydrogen and producing hydrogen by electrolyzing water, with an open circuit voltage of more than 1.15V and a maximum power generation of 0.45W / cm 2 The above has a good industrialization prospect. However, the preparation method of the barrier layer requires mixing large and small particles of raw materials, and the thickness of the barrier layer is 5 to 20 μm. The raw material system of this method is complex, the thickness of the barrier layer is thick, and it is not easy to control the process to prepare large-area single cells.
[0007] CN111574244B discloses a method for densifying a barrier layer of a solid oxide battery. The method comprises: mixing Ge(NO3)3·6H2O and Ce(NO3)3·6H2O in a molar ratio of 0.1:0.9 (Ce 0.9 G 0.1 O 2-m ) is prepared into a hydrothermal solution, and the battery with the GDC barrier layer printed on it is reacted at 180°C for 24 hours by a hydrothermal method, and then a complete battery is prepared, so that the obtained battery has higher conductivity and catalytic activity and lower ohmic impedance. However, this method uses screen printing to prepare the barrier layer and uses hydrothermal reaction to improve its density, which has the disadvantages of complex process, limited substrate material and size, and is not suitable for preparing large-area single cells.
[0008] CN114725461A discloses a low-temperature sintered densified samarium-neodymium co-doped cerium oxide-based barrier layer and a preparation method thereof. The samarium-neodymium co-doped cerium oxide-based barrier layer is a sintered densified samarium-neodymium co-doped cerium oxide-based barrier layer; the density of the samarium-neodymium co-doped cerium oxide-based barrier layer is more than 90%. The preparation method of the barrier layer adds soluble iron salts and / or soluble manganese salts in the process of synthesizing doped cerium oxide-based powders, and adopts a solid-liquid composite method to synthesize the powder, so that SNDC can be obtained at a lower sintering temperature. However, this method requires the preparation of modified samarium-neodymium co-doped cerium oxide-based powders first, and this process includes the use of soluble iron salts and / or soluble manganese salts and complexing agents to prepare a precursor solution, and then heat treatment is required. The formula of the precursor is complicated and the preparation process is cumbersome.
[0009] CN104269563A discloses a method for preparing a cathode barrier layer of a metal-supported solid oxide fuel cell. The method comprises the following steps: adding cathode barrier layer material powder to an ethyl cellulose pine alcohol solution in proportion, grinding to obtain a slurry; depositing the slurry on a half-cell of a porous metal support layer thick film / porous metal ceramic gradient transition layer film / porous anode layer film / dense electrolyte layer film by screen printing; sintering at 1000-1200°C for 2-4 hours in a vacuum atmosphere, controlling the temperature rise and fall rates to 0.5-5°C / min, and cooling to room temperature to obtain a cathode barrier layer. The method sintering the cathode barrier layer in a low vacuum atmosphere at high temperature can avoid excessive oxidation of the support body, and film shedding caused by reduction of cerium valence in the cerium oxide barrier layer in a reducing atmosphere, and also avoids the volatility loss of Ga in the LaGaO3-based barrier layer, thereby effectively blocking the reaction of high-performance cathode materials with zirconium oxide-based solid electrolytes under preparation conditions. However, the barrier layer prepared by the method using screen printing has a thickness of 3 to 10 μm and requires vacuum sintering (0.1 to 10 Pa). The sintering conditions of the method are complex and the thickness of the prepared barrier layer is relatively thick.
[0010] CN220821635U discloses a bipolar plate assembly, which includes two graphite layers and at least one permeation barrier layer, the permeation barrier layer is sandwiched between the two graphite layers, and the permeation barrier layer has a permeability lower than that of the graphite layer. The bipolar plate assembly is used for proton exchange membrane fuel cells. The permeation barrier layer can be made of any suitable transition metal, such as Ti (titanium), Ni (nickel), W (tungsten), Nb (niobium), etc., and suitable non-transition metals can also be used, such as Cu (copper), Al (aluminum), Zn (zinc), etc. Due to the setting of the permeation barrier layer, the permeability of the conductive structure to the reaction gas can be reduced. At the same time, the permeation barrier layer also has a certain conductivity to further increase the conductivity of the conductive structure. However, the bipolar plate assembly is not used for solid oxide batteries, and the material of the permeation barrier layer is a metal or alloy, which functions to reduce gas permeation and increase conductivity, which is different from the material and function of the barrier layer in the solid oxide battery.
[0011] It can be seen from the above prior art that most of the barrier layers of current solid oxide batteries have problems such as complex raw material system and / or preparation process, or thick thickness, or poor density and / or uniformity, and are not suitable for preparing large-area single cells. Summary of the invention
[0012] In order to solve at least one of the above technical problems, the purpose of the present invention is to provide a barrier layer and a preparation method thereof and a solid oxide battery. The barrier layer prepared by the present invention has the advantages of high density, and the preparation process and raw material system of the barrier layer are relatively simple. The barrier layer is suitable for large-area single cells.
[0013] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a barrier layer, which comprises the following steps:
[0014] S1, at least cerium-based oxide powder, a sintering aid and a solvent are uniformly mixed to obtain a slurry;
[0015] S2, spin coating the slurry on a substrate, and sintering the slurry to obtain the barrier layer;
[0016] Wherein, the sintering aid includes oxides and / or salt compounds of one or more metals selected from Co, Cu, Bi, Li, Zn, Al and Ni.
[0017] According to a specific embodiment of the present invention, preferably, in step S1, the cerium-based oxide powder includes one or a combination of gadolinium-doped cerium oxide (GDC) powder, samarium-doped cerium oxide (SDC) powder and lanthanum-doped cerium oxide (LDC) powder.
[0018] According to a specific embodiment of the present invention, preferably, in step S1, the average particle size of the cerium-based oxide powder is 0.01 to 1 μm, more preferably 0.05 to 0.5 μm.
[0019] According to a specific embodiment of the present invention, preferably, in step S1, based on the mass of the slurry being 100%, the content of the cerium-based oxide powder therein is 20% to 70%, more preferably 30% to 40%.
[0020] According to a specific embodiment of the present invention, preferably, in step S1, the sintering aid includes oxides and / or salt compounds of one or more metals selected from Co, Cu and Bi.
[0021] According to a specific embodiment of the present invention, preferably, in step S1, the mass ratio of the sintering aid to the cerium-based oxide powder is 0.5% to 5%, more preferably 1% to 3%.
[0022] According to a specific embodiment of the present invention, preferably, in step S1, the slurry further comprises a binder. More preferably, the mass ratio of the binder to the cerium-based oxide powder is 0.5% to 8%.
[0023] According to a specific embodiment of the present invention, preferably, in step S2, the substrate includes at least one of a fuel electrode supported half-cell, an electrolyte supported half-cell, a metal supported half-cell, an air electrode supported half-cell, and the like.
[0024] According to a specific embodiment of the present invention, preferably, in step S2, the spin coating rate is 500-5000 rpm, more preferably 1500-3000 rpm.
[0025] According to a specific embodiment of the present invention, preferably, in step S2, the spin coating time is 0.5 to 5 minutes, more preferably 1 to 2 minutes.
[0026] According to a specific embodiment of the present invention, preferably, in step S2, the spin coating is performed once.
[0027] According to a specific embodiment of the present invention, preferably, in step S2, the sintering temperature is 1200-1400°C, more preferably 1225-1275°C.
[0028] According to a specific embodiment of the present invention, preferably, in step S2, the sintering time is 1 to 10 hours.
[0029] According to a specific embodiment of the present invention, preferably, in step S2, the thickness of the barrier layer is 0.5 to 8 μm, more preferably 1 to 3 μm.
[0030] A second aspect of the present invention provides a barrier layer, which is prepared by the above-mentioned method for preparing a barrier layer.
[0031] According to a specific embodiment of the present invention, preferably, the density of the barrier layer is >73%.
[0032] According to a specific embodiment of the present invention, preferably, the interface bonding strength of the barrier layer is >10 MPa.
[0033] According to a specific embodiment of the present invention, preferably, the thickness uniformity of the barrier layer is >94%.
[0034] A third aspect of the present invention provides a solid oxide battery, which at least comprises the above-mentioned barrier layer.
[0035] The technical solution of the present invention achieves at least the following beneficial effects:
[0036] The present invention uses cerium-based oxide powder as a raw material, and produces a synergistic effect with a sintering aid. Under the condition of spin coating once and at a low sintering temperature, a barrier layer with good density and uniformity and thin thickness can be prepared. In addition, the barrier layer of the present invention also has a high interface bonding strength. The preparation method of the barrier layer of the present invention has the advantages of a relatively simple raw material system and a relatively simple preparation process. At the same time, since the preparation process of the present invention is relatively simple and the sintering temperature is relatively low, the present invention also has the advantages of saving time cost and reducing energy consumption. The barrier layer of the present invention is suitable for large-area single cells. In the case of a large area, the barrier layer of the present invention still maintains a high uniformity and flatness. In practical applications, the barrier layer of the present invention can avoid the reaction between the YSZ electrolyte and the LSCF cathode to generate La2Zr2O7 and SrZrO3 insulating phases. At the same time, since the sintering temperature of the present invention is relatively low, the generation of a high-impedance Ce-Zr solid solution phase is avoided. Therefore, the solid oxide battery (i.e., SOFC / SOEC single cell) of the present invention has improved stability and chemical compatibility between components, and has very high practicality and commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic flow chart of the method for preparing the barrier layer and the single cell provided in Examples 1-5.
[0038] Figure 2 Schematic diagram of the structure of the barrier layer and single cell provided in Examples 1-5.
[0039] Figure 3 This is a scanning electron microscope photograph of the barrier layer 2 of Example 1.
[0040] Figure 4 This is a microstructure diagram of the single cell of Example 1.
[0041] Figure 5 This is a scanning electron microscope photograph of the barrier layer 2 of Example 2.
[0042] Figure 6 This is a scanning electron microscope photograph of the barrier layer 2 of Example 3.
[0043] Figure 7 This is a scanning electron microscope photograph of the barrier layer 2 of Example 4.
[0044] Figure 8 The battery power-voltage-current diagram of the single battery of Examples 1-4.
[0045] Fig. 9 This is a scanning electron microscope photograph of the barrier layer 2 of Example 5.
[0046] Fig.10 This is a scanning electron microscope photograph of the barrier layer 2 of Comparative Example 1.
[0047] Fig.11 This is a scanning electron microscope photograph of the barrier layer 2 of Comparative Example 2.
[0048] Fig.12 This is a scanning electron microscope photograph of the barrier layer 2 of Comparative Example 3.
[0049] Fig.13 It is the battery power-voltage-current diagram of the single battery of comparative example 1-3.
[0050] Description of Figure Numbers:
[0051] 1- fuel electrode support type half-cell; 2- barrier layer; 3- air electrode layer; 101- support layer; 102- fuel electrode layer; 103- electrolyte layer. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments of the present invention and the technical features in the embodiments can be combined with each other without conflict.
[0053] It should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0054] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0055] According to a specific embodiment of the first aspect of the present invention, the present invention provides a method for preparing a barrier layer, which comprises the following steps:
[0056] S1, at least cerium-based oxide powder, a sintering aid and a solvent are uniformly mixed to obtain a slurry;
[0057] S2, spin coating the slurry on a substrate, and sintering the slurry to obtain the barrier layer;
[0058] Wherein, the sintering aid includes oxides and / or salt compounds of one or more metals selected from Co, Cu, Bi, Li, Zn, Al and Ni.
[0059] In some embodiments, in step S1, the cerium-based oxide powder includes but is not limited to one or a combination of gadolinium-doped cerium oxide (GDC) powder, samarium-doped cerium oxide (SDC) powder, and lanthanum-doped cerium oxide (LDC) powder, and is preferably gadolinium-doped cerium oxide (GDC).
[0060] In some embodiments, in step S1, the average particle size of the cerium-based oxide powder is 0.01 to 1 μm, for example but not limited to: 0.01 μm, 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, etc., preferably 0.05 to 0.5 μm.
[0061] In some embodiments, in step S1, the cerium-based oxide powder includes a combination of a first powder and a second powder, the first powder has an average particle size of 10-100nm, and the second powder has an average particle size of greater than 100nm to 500nm; preferably, the first powder has an average particle size of 10-90nm, and the second powder has an average particle size of 150nm to 500nm.
[0062] In some embodiments, in step S1, the mass ratio of the first powder to the second powder is 1:2 to 2:1, preferably 1:1.
[0063] In some embodiments, in step S1, based on the mass of the slurry being 100%, the content of the cerium-based oxide powder therein is 20% to 70%, for example but not limited to: 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc., preferably 30% to 40%.
[0064] In some embodiments, in step S1, the sintering aid includes oxides and / or salt compounds of one or more metals selected from Co, Cu and Bi, preferably oxides of Co and / or Cu, more preferably oxides of Co, such as one or a combination of CoO, Co2O3 and Co3O4.
[0065] In some embodiments, in step S1, the mass ratio of the sintering aid to the cerium-based oxide powder is 0.5% to 5%, for example but not limited to: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4% or 5%, etc., preferably 1% to 3%.
[0066] In some embodiments, in step S1, the solvent includes but is not limited to one or a combination of water, ethanol, ethylene glycol, and isopropanol, etc., preferably ethanol.
[0067] In some embodiments, in step S1 , the slurry further includes a binder.
[0068] In some embodiments, in step S1, the binder includes but is not limited to one or a combination of polyvinyl alcohol (PVA), polyvinyl butyral (PVB), ethyl cellulose (EC), etc.
[0069] In some embodiments, in step S1, the mass ratio of the binder to the cerium-based oxide powder is 0.5% to 8%, for example but not limited to: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7% or 8%, etc., preferably 1% to 3%.
[0070] In some embodiments, in step S1, the slurry further includes a dispersant. Preferably, the dispersant includes but is not limited to at least one of polyethylene glycol (PEG) and oleic acid (OA). More preferably, the mass ratio of the dispersant to the cerium-based oxide powder is 0.5% to 8%, for example but not limited to: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7% or 8%, etc.
[0071] In some embodiments, in step S1, the slurry further includes a plasticizer. Preferably, the plasticizer includes but is not limited to at least one of dibutyl phthalate (DBP) and acetyl trioctyl citrate (ATOC). More preferably, the mass ratio of the plasticizer to the cerium-based oxide powder is 0.5% to 5%, for example but not limited to: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4% or 5%, etc.
[0072] In some embodiments, in step S2, the substrate includes but is not limited to at least one of a fuel electrode supported half-cell, an electrolyte supported half-cell, a metal supported half-cell, and an air electrode supported half-cell. These types of half-cells can all be half-cells disclosed in the prior art. The present invention does not impose any special restrictions on the structures of these half-cells.
[0073] Specifically, taking the fuel pole support type half-cell as an example, it may include a support layer, a fuel pole layer and an electrolyte layer from bottom to top. Among them, the materials of the support layer and the fuel pole layer include but are not limited to at least one of Ni-YSZ, Ni-ScSZ (i.e. nickel-scandium yttrium stabilized zirconia), Ni-SDC, Ni-GDC and Cu-GDC, etc., preferably Ni-YSZ. The material of the electrolyte layer includes but is not limited to at least one of YSZ, GDC, SDC, LDC and ScSZ, etc., preferably YSZ. In a preferred embodiment, the material of the fuel pole support type half-cell is NiO-YSZ / YSZ, that is, the materials of the support layer and the fuel pole layer are Ni-YSZ, respectively, and the material of the electrolyte layer is YSZ.
[0074] In some embodiments, in step S2, the spin coating rate is 500-5000 rpm, for example but not limited to: 500 rpm, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm or 5000 rpm, etc., preferably 1500-3000 rpm.
[0075] In some embodiments, in step S2, the spin coating time is 0.5 to 5 min, for example but not limited to: 0.5 min, 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min or 5 min, etc., preferably 1 to 2 min.
[0076] In some embodiments, in step S2, the spin coating is performed once.
[0077] In some embodiments, in step S2, after the spin coating is completed, drying may be performed selectively.
[0078] In some embodiments, in step S2, the sintering temperature is 1200-1400°C, for example but not limited to: 1200°C, 1225°C, 1250°C, 1275°C, 1300°C, 1325°C, 1350°C, 1375°C or 1400°C, etc., preferably 1225-1275°C.
[0079] In some embodiments, in step S2, the sintering time is 1 to 10 hours, for example but not limited to: 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, etc., preferably 3 to 5 hours.
[0080] In some embodiments, in step S2, the thickness of the barrier layer is 0.5 to 8 μm, for example but not limited to: 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm, etc., preferably 1 to 3 μm.
[0081] According to a specific embodiment of the second aspect of the present invention, the present invention provides a barrier layer, which is prepared by the above-mentioned method for preparing a barrier layer.
[0082] In some embodiments, the density of the barrier layer is >73%. The density test method includes the following steps: quantitatively evaluating the surface density of the barrier layer using ImageJ, importing the surface scanning electron microscope photo of the barrier layer into ImageJ, and then identifying and quantifying the pores, and calculating the density using the following formula: Density (%) = (total area of the barrier layer - area of the pores in the barrier layer) / total area of the barrier layer × 100%. The barrier layer to be tested is a circular barrier layer with a diameter of 16 mm or an area of 10 × 10 cm 2 Square barrier layer.
[0083] In some embodiments, the interfacial bonding strength of the barrier layer is greater than 10 MPa. The test method for the interfacial bonding strength comprises the following steps: fixing one side of the substrate on which the barrier layer is formed, and adhering the other side (i.e., one side of the barrier layer) to a tensile gauge, applying a tensile force per unit area in a direction perpendicular to the substrate on which the barrier layer is formed, and when the barrier layer falls off from the substrate, the applied tensile stress is the interfacial bonding strength. The barrier layer to be tested is a circular barrier layer with a diameter of 16 mm.
[0084] In some embodiments, the thickness uniformity of the barrier layer is >94%. The thickness uniformity test method includes the following steps: using a scanning electron microscope to test the cross-sectional images of the center and 5 to 6 mm near the edge of the substrate on which the barrier layer is formed, and then identifying and quantifying the thickness of the barrier layer. The thickness uniformity calculation formula is: thickness uniformity (%) = [1-(barrier layer thickness at the center - barrier layer thickness at 5 to 6 mm near the edge) / barrier layer thickness at the center] × 100%. The barrier layer to be tested is an area of 10 × 10 cm 2 Square barrier layer.
[0085] The present invention adopts cerium-based oxide powder with a specific particle size and a specific sintering aid as raw materials, especially adopts GDC powder with a specific particle size and Co oxide as raw materials, and combines the specific content of cerium-based oxide powder in the slurry and the specific mass ratio of the sintering aid to the cerium-based oxide powder, so that the best synergistic effect is produced therebetween, and combines the specific spin coating rate and spin coating time of the present invention, so that the present invention can prepare a barrier layer with excellent density and uniformity, high interface strength and thin thickness under the condition of one spin coating and a relatively low sintering temperature.
[0086] According to a specific embodiment of the third aspect of the present invention, the present invention provides a solid oxide battery, which at least includes the above-mentioned barrier layer.
[0087] In some embodiments, as described above, the substrate includes but is not limited to at least one of a fuel electrode supported half-cell, an electrolyte supported half-cell, a metal supported half-cell and an air electrode supported half-cell, and the barrier layer is formed on the substrate. Based on this, those skilled in the art can select the functional layer that the solid oxide battery further includes on the barrier layer according to the substrate specifically used in the present invention.
[0088] Specifically, in some embodiments, the solid oxide battery further includes an air electrode layer, and the air electrode layer is disposed on the barrier layer.
[0089] In some embodiments, the material of the air electrode layer includes but is not limited to at least one of LSC-GDC (i.e., lanthanum strontium cobalt oxide-gadolinium doped cerium oxide), LSCF-GDC (i.e., lanthanum strontium cobalt iron oxide-gadolinium doped cerium oxide), LSTF-GDC (i.e., lanthanum strontium titanium iron oxide-gadolinium doped cerium oxide), LNO-GDC (lanthanum nickelate oxide-gadolinium doped cerium oxide), etc., preferably LSCF-GDC.
[0090] In some embodiments, the air electrode layer is formed on the barrier layer by coating the slurry of the air electrode layer on the barrier layer, and then sintering to obtain the air electrode layer. Specifically, the method of coating the slurry of the air electrode layer on the barrier layer may include but is not limited to at least one of screen printing, spin coating, etc. After coating, drying may be performed selectively. In addition, the sintering temperature may be 900 to 1200°C, preferably 1000 to 1100°C; the sintering time may be 1 to 5 hours, preferably 1 to 3 hours.
[0091] In some embodiments, the thickness of the air electrode layer is 5 to 50 μm.
[0092] In some embodiments, specifically, the solid oxide cell includes, from bottom to top, the fuel electrode supporting half-cell, the barrier layer and the air electrode layer.
[0093] The solid oxide battery of the present invention has improved stability and chemical compatibility between components and can be used as a large-area single battery.
[0094] The technical solutions of the present invention are specifically described below by way of examples, but the present invention is not limited to these examples and can of course be implemented in various modifications within the scope of the gist of the present invention.
[0095] Example 1
[0096] like Figure 1 and Figure 2 As shown, 2.0g of GDC powder with an average particle size of 200nm, 0.04g of binder PVB, 0.02g of sintering aid Co3O4 and 4g of solvent ethanol are mixed evenly to obtain a slurry (the content of GDC powder is about 33% based on the mass of the slurry as 100%); the fuel electrode support type half-cell 1 is used as the substrate, the substrate is fixed on the spin coater, and an appropriate amount of slurry is dripped on the surface of the substrate, and after spin coating at a speed of 1500rpm for 2min, it is dried and placed in a muffle furnace, and sintered at 1250℃ for 5h to obtain a barrier layer 2. Scanning electron microscopy test shows that the thickness of the barrier layer 2 is 1.1μm. Figure 3 : is a scanning electron microscope photograph of the barrier layer 2 of this embodiment. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0097] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050°C for 2 hours to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components of the LSCF-GDC slurry are: 50wt% LSCF and 50wt% GDC. Scanning electron microscopy test showed that the thickness of the air electrode layer 3 was 28μm.
[0098] like Figure 2 As shown, the single cell of this embodiment includes, from bottom to top, a fuel electrode support type half-cell 1, a barrier layer 2 and an air electrode layer 3, wherein the fuel electrode support type half-cell 1 includes, from bottom to top, a support layer 101, a fuel electrode layer 102 and an electrolyte layer 103. The material of the fuel electrode support type half-cell 1 is NiO-YSZ / YSZ, wherein the materials of the support layer 101 and the fuel electrode layer 102 are Ni-YSZ respectively, and the material of the electrolyte layer 103 is YSZ.
[0099] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 79.1% and the interface bonding strength was 15 MPa.
[0100] A large-area single cell was prepared by the method of this embodiment, and its microstructure is as follows: Figure 4 As shown. In the case of enlarged preparation, the area of the large-area single cell of this embodiment is 10×10cm 2 The density of the barrier layer 2 of the battery is 78.3%, which is almost not reduced compared with the barrier layer 2 of the small area mentioned above. In addition, the thickness uniformity of the barrier layer 2 is 97%, which has a high uniformity. At the same time, the barrier layer 2 and the substrate were tested by confocal microscopy, and it was found that the flatness of the barrier layer 2 was basically consistent with that of the substrate.
[0101] The single cell (active area 0.785 cm 2 The peak power density of the battery at 800°C was 805 mW / cm 2 The test conditions are: using the four-electrode method, silver wires as current and voltage leads, hydrogen as fuel, and air as oxidant.
[0102] Example 2
[0103] like Figure 1 and Figure 2 As shown, 2.0g of GDC powder with an average particle size of 200nm, 0.04g of binder PVB, 0.02g of sintering aid Bi2O3 and 4g of solvent ethanol are mixed evenly to obtain a slurry (the content of GDC powder is about 33% based on the mass of the slurry as 100%); the fuel electrode support type half-cell 1 is used as the substrate, the substrate is fixed on the spin coater, and an appropriate amount of slurry is dripped on the surface of the substrate, and after spin coating at a speed of 1500rpm for 2min, it is dried and placed in a muffle furnace, and sintered at 1250℃ for 5h to obtain a barrier layer 2. Scanning electron microscopy test shows that the thickness of the barrier layer 2 is 1.2μm. Figure 5 : is a scanning electron microscope photograph of the barrier layer 2 of this embodiment. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0104] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050°C for 2h to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components and contents of the LSCF-GDC slurry were the same as those in Example 1. Scanning electron microscopy showed that the thickness of the air electrode layer 3 was 26 μm.
[0105] like Figure 2 As shown, the structure of the single cell of this embodiment is the same as that of the first embodiment.
[0106] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 73.2% and the interface bonding strength was 12 MPa.
[0107] The single cell (active area 0.785 cm 2 ) The peak power density at 800°C is 734 mW / cm 2 The test conditions are the same as those in Example 1.
[0108] Example 3
[0109] like Figure 1 and Figure 2 As shown, 2.5g of GDC powder with an average particle size of 200nm, 0.05g of binder PVB, 0.025g of sintering aid Co3O4 and 4g of solvent ethanol are mixed evenly to obtain a slurry (the content of GDC powder is about 38% based on the mass of the slurry as 100%); the fuel electrode support type half-cell 1 is used as the substrate, the substrate is fixed on the spin coater, and an appropriate amount of slurry is dripped on the surface of the substrate, and after spin coating at a speed of 1500rpm for 2min, it is dried and placed in a muffle furnace, and sintered at 1250℃ for 5h to obtain a barrier layer 2. Scanning electron microscopy test shows that the thickness of the barrier layer 2 is 1.7μm. Figure 6 : is a scanning electron microscope photograph of the barrier layer 2 of this embodiment. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0110] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050° C. for 2 hours to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components and contents of the LSCF-GDC slurry were the same as those in Example 1. Scanning electron microscopy showed that the thickness of the air electrode layer 3 was 27 μm.
[0111] like Figure 2 As shown, the structure of the single cell of this embodiment is the same as that of the first embodiment.
[0112] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 79.6% and the interface bonding strength was 16 MPa.
[0113] The single cell (active area 0.785 cm 2 ) The peak power density at 800°C is 692 mW / cm 2 The test conditions are the same as those in Example 1.
[0114] Example 4
[0115] like Figure 1 and Figure 2 As shown, 2.0 g of GDC powder with an average particle size of 200 nm, 0.04 g of binder PVB, 0.02 g of sintering aid CuO, 0.05 g of dispersant PEG and 4 g of solvent ethanol are mixed evenly to obtain a slurry (the content of GDC powder is about 32.7% based on the mass of the slurry as 100%); the fuel electrode support type half-cell 1 is used as a substrate, the substrate is fixed on a spin coater, an appropriate amount of slurry is dripped on the surface of the substrate, and after spin coating at a speed of 1500 rpm for 2 minutes, it is dried and placed in a muffle furnace, sintered at 1250°C for 5 hours to obtain a barrier layer 2. Scanning electron microscopy test shows that the thickness of the barrier layer 2 is 1.4 μm. Figure 7 : is a scanning electron microscope photograph of the barrier layer 2 of this embodiment. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0116] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050° C. for 2 hours to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components and contents of the LSCF-GDC slurry were the same as those in Example 1. Scanning electron microscopy showed that the thickness of the air electrode layer 3 was 28 μm.
[0117] like Figure 2 As shown, the structure of the single cell of this embodiment is the same as that of the first embodiment.
[0118] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 78.9% and the interface bonding strength was 14 MPa.
[0119] The single cell (active area 0.785 cm 2 ) The peak power density at 800°C is 826 mW / cm 2The test conditions are the same as those in Example 1.
[0120] Figure 8 The battery power-voltage-current diagram of the single battery of Examples 1-4.
[0121] Example 5
[0122] like Figure 1 and Figure 2 As shown, 1.0g of GDC powder with an average particle size of 200nm and 50nm, 0.04g of binder PVB, 0.02g of sintering aid Co3O4 and 4g of solvent ethanol are mixed evenly to obtain a slurry (the content of GDC powder is about 33% based on the mass of the slurry as 100%); the fuel electrode support type half-cell 1 is used as the substrate, the substrate is fixed on the spin coater, an appropriate amount of slurry is dripped on the surface of the substrate, and after spin coating at a speed of 1500rpm for 2min, it is dried and placed in a muffle furnace, sintered at 1250℃ for 5h to obtain a barrier layer 2. Scanning electron microscope test shows that the thickness of the barrier layer 2 is 1.9μm. Fig. 9 : is a scanning electron microscope photograph of the barrier layer 2 of this embodiment. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0123] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050°C for 2 hours to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components of the LSCF-GDC slurry are: 50wt% LSCF and 50wt% GDC. Scanning electron microscopy test showed that the thickness of the air electrode layer 3 was 27μm.
[0124] like Figure 2 As shown, the structure of the single cell of this embodiment is the same as that of the first embodiment.
[0125] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 81.9% and the interface bonding strength was 17 MPa.
[0126] The single cell (active area 0.785 cm 2 ) The peak power density at 800°C is 761 mW / cm 2 The test conditions are the same as those in Example 1.
[0127] Comparative Example 1
[0128] 2.0 g of GDC powder with an average particle size of 200 nm, 0.04 g of binder PVB and 4 g of solvent ethanol were mixed evenly to obtain slurry; the fuel electrode support type half-cell 1 was used as the substrate, the substrate was fixed on the spin coater, an appropriate amount of slurry was dripped on the surface of the substrate, and the substrate was spin-coated at a speed of 1500 rpm for 2 minutes, and then dried, placed in a muffle furnace, and sintered at 1250°C for 5 hours to obtain a barrier layer 2. The thickness of the barrier layer 2 was 2.3 μm as determined by scanning electron microscopy. Fig.10 The scanning electron microscope photograph of the barrier layer 2 of this comparative example is shown in FIG. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0129] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050°C for 2h to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components and contents of the LSCF-GDC slurry were the same as those in Example 1. Scanning electron microscopy showed that the thickness of the air electrode layer 3 was 26 μm.
[0130] The structure of the single cell of this comparative example is the same as that of Example 1.
[0131] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 72.8% and the interface bonding strength was 14 MPa.
[0132] The peak power density of the single cell of this comparative example was tested at 800°C, and the result was 686 mW / cm 2 The test conditions are the same as those in Example 1.
[0133] Comparative Example 2
[0134] 2.0g of GDC powder with an average particle size of 200nm, 0.04g of binder PVB, 0.02g of sintering aid Fe3O4 and 4g of solvent ethanol were mixed evenly to obtain slurry; the fuel electrode support type half-cell 1 was used as the substrate, the substrate was fixed on the spin coater, an appropriate amount of slurry was dripped on the surface of the substrate, and the substrate was spin-coated at a speed of 1500rpm for 2min, dried, placed in a muffle furnace, and sintered at 1250℃ for 5h to obtain a barrier layer 2. Scanning electron microscopy test showed that the thickness of the barrier layer 2 was 1.2μm. Fig.11 The scanning electron microscope photograph of the barrier layer 2 of this comparative example is shown in FIG. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0135] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050° C. for 2 hours to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components and contents of the LSCF-GDC slurry were the same as those in Example 1. Scanning electron microscopy showed that the thickness of the air electrode layer 3 was 28 μm.
[0136] The structure of the single cell of this comparative example is the same as that of Example 1.
[0137] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 76.4% and the interface bonding strength was 15 MPa.
[0138] The peak power density of the single cell of this comparative example was tested at 800°C, and the result was 627mW / cm 2 The test conditions are the same as those in Example 1.
[0139] Comparative Example 3
[0140] 2.0 g of GDC powder with an average particle size of 200 nm, 0.04 g of binder PVB, 0.02 g of sintering aid Fe(NO3)2 and 4 g of solvent ethanol were mixed evenly to obtain slurry; the fuel electrode support type half-cell 1 was used as the substrate, the substrate was fixed on the spin coater, an appropriate amount of slurry was dripped on the surface of the substrate, and the substrate was spin-coated at a speed of 1500 rpm for 2 minutes, dried, placed in a muffle furnace, and sintered at 1250°C for 5 hours to obtain a barrier layer 2. Scanning electron microscopy test showed that the thickness of the barrier layer 2 was 1.8 μm. Fig.12 The scanning electron microscope photograph of the barrier layer 2 of this comparative example is shown in FIG. The plane size and shape of the barrier layer 2 is a circle with a diameter of 16 mm.
[0141] Afterwards, LSCF-GDC slurry was screen-printed on the barrier layer 2, dried, placed in a muffle furnace, and sintered at 1050° C. for 2 hours to obtain an air electrode layer 3, and then a solid oxide single cell was obtained. The components and contents of the LSCF-GDC slurry were the same as those in Example 1. Scanning electron microscopy showed that the thickness of the air electrode layer 3 was 25 μm.
[0142] The structure of the single cell of this comparative example is the same as that of Example 1.
[0143] The density and interface bonding strength of the barrier layer 2 were tested using the method described above, and the results were: the density was 63.9% and the interface bonding strength was 11 MPa.
[0144] The peak power density of the single cell of this comparative example was tested at 800°C, and the result was 639 mW / cm 2The test conditions are the same as those in Example 1.
[0145] Fig.13 The battery power-voltage-current diagram of the single battery of Comparative Examples 1-3.
Claims
1. A method for preparing a barrier layer, comprising the following steps: S1, at least cerium-based oxide powder, a sintering aid and a solvent are uniformly mixed to obtain a slurry; S2, spin coating the slurry on a substrate, and sintering the slurry to obtain the barrier layer; Wherein, the sintering aid includes oxides and / or salt compounds of one or more metals selected from Co, Cu, Bi, Li, Zn, Al and Ni.
2. The method for preparing a barrier layer according to claim 1, wherein: In step S1, the cerium-based oxide powder includes one or a combination of gadolinium-doped cerium oxide powder, samarium-doped cerium oxide powder and lanthanum-doped cerium oxide powder.
3. The method for preparing a barrier layer according to claim 1, wherein: In step S1, the average particle size of the cerium-based oxide powder is 0.01 to 1 μm, preferably 0.05 to 0.5 μm.
4. The method for preparing a barrier layer according to claim 1, wherein: In step S1, based on the mass of the slurry being 100%, the content of the cerium-based oxide powder therein is 20% to 70%, preferably 30% to 40%.
5. The method for preparing a barrier layer according to claim 1, wherein: In step S1, the sintering aid includes oxides and / or salt compounds of one or more metals selected from Co, Cu and Bi.
6. The method for preparing a barrier layer according to claim 1, wherein: In step S1, the mass ratio of the sintering aid to the cerium-based oxide powder is 0.5% to 5%, preferably 1% to 3%.
7. The method for preparing a barrier layer according to claim 1, wherein: In step S1, the slurry further includes a binder; Preferably, the mass ratio of the binder to the cerium-based oxide powder is 0.5% to 8%.
8. The method for preparing a barrier layer according to claim 1, wherein: In step S2, the substrate includes at least one of a fuel electrode supported half cell, an electrolyte supported half cell, a metal supported half cell, and an air electrode supported half cell.
9. The method for preparing a barrier layer according to claim 1, wherein: In step S2, the spin coating speed is 500-5000 rpm, preferably 1500-3000 rpm.
10. The method for preparing a barrier layer according to claim 9, wherein: In step S2, the spin coating time is 0.5 to 5 minutes, preferably 1 to 2 minutes.
11. The method for preparing a barrier layer according to claim 1, wherein: In step S2, the spin coating is performed once.
12. The method for preparing a barrier layer according to claim 1, wherein: In step S2, the sintering temperature is 1200-1400°C, preferably 1225-1275°C.
13. The method for preparing a barrier layer according to claim 12, wherein: In step S2, the sintering time is 1 to 10 hours.
14. The method for preparing a barrier layer according to claim 1, wherein: In step S2, the thickness of the barrier layer is 0.5-8 μm, preferably 1-3 μm.
15. A barrier layer, which is prepared by the method for preparing a barrier layer according to any one of claims 1 to 14; Preferably, the density of the barrier layer is >73%; Preferably, the interfacial bonding strength of the barrier layer is >10MPa; Preferably, the thickness uniformity of the barrier layer is >94%.
16. A solid oxide battery comprising at least the barrier layer according to claim 15.
Citation Information
Patent Citations
Preparation method of cathode barrier layer of metallic-propping solid oxide fuel cell
CN104269563A
A method for densifying the barrier layer of a solid oxide battery
CN111574244B
A coating for preparing a barrier layer, a method for preparing the barrier layer, and the barrier layer itself.
CN113929498B
Bipolar plate assembly of fuel cell stack and fuel cell stack
CN220821635U
Method for low-temperature sintering densification of cerium oxide-based insulating layer in fuel cell
CN109836154A